Alfonso de Castro on Vernacular Bible Translation and Christian Education - Crom, Dries De (Journal of Early Modern Christianity, 2020)
Alfonso de Castro (1495-1558) is known as a staunch opponent of vernacular Bible translation, who intervened on the matter at the Council of Trent. This article offers a fresh appreciation of Castro’s polemics against vernacular bibles, in light of a less well-known treatise in which Castro defends the right of the indigenous Spanish colonial population to be educated in the liberal arts and theology. It is argued that at the root of Castro’s misgivings about Bible translation is a concern for preserving traditional education as a necessary prerequisite for biblical interpretation.